Costume design in Assassin's Creed III: a comparative study between the real and the virtual - Dykes, Michèle (My University, 2014)
This paper presents a detailed analysis of Assassin’s Creed III’s character Haytham Kenway’s costume, with emphasis on the physical qualities as well as the symbolic factors used in the garments. The costume is constructed physically in order to facilitate a further comparative study between the real and the virtual qualities looking at historical and technical accuracies in order to aid game companies in constructing accurate virtual costume.
Keywords: Clothing and dress--History.; Costume.